Dosis de ceniza de madera y sus efectos en los componentes agronómicos y rendimiento de Vigna unguiculata L. subsp sesquipedalis Chiclayo verdura, en Zungarocoha-Loreto.2022 - Correa Pinedo, Kevin Esmith (2022)
The research "Dose of wood ash and its effects on the agronomic components and yield of Vigna unguiculata L. subsp sesquipedalis Chiclayo vegetable, in Zungarococha-Loreto.2022", was carried out in the experimental area of the Horticultural Plants Workshop, of the Faculty of Agronomy-UNAP, where six dependent variables were evaluated (plant height, pod length, number of pods/plant, weight of pod, weight of pods/plant and weight of pods/ha due to different amounts of wood ash (1, 2 and 3 t/ha) and a control treatment without fertilization. The general objective was to evaluate the effects of wood ash doses on the agronomic components and yield of Vigna unguiculata L. subsp sesquipedalis Chiclayo vegetable, in Zungarococha-Loreto.2022. The experimental design applied was the DBCA, with its respective analysis of variance and its Tukey comparison test. reaching the following conclusions: The T4 Treatment with 3 t of wood ash / ha, presented the best plant height (220 cm), pod length (70 cm) pod weight (39 g), number of pods / plant (34 units), weight of pods / plant (1,333.75 g) and weight of pods / ha (26,675 Kg) and also obtained the best productivity with S / .68,222.00